(untitled) (Damascus University Journal of agriculture sciences, 2025)
Abstract This research was conducted in 2022-2023 in the Laboratory of Pesticides Research - Department of Plant Protection - faculty of Agriculture - University of Damascus, to evaluate the effectiveness of essential oils and oily hexane extracts of rosemary (Rosmarinus officinalis L.), lavender (Lavandula angustifolia Mill) and oregano (Origanum vulgare L.) from the Lamiaceae family, and the result of loading them on silicon nanoparticles (SiO2) in inhibiting mycelium the fungus Botrytis cinerea on the PDA medium in the laboratory. The results showed the superiority of the essential oil of oreganoloaded on silica nanoparticles significantly compared with all the treatments in inhibiting the growth of the fungus B. cinerea in the medium. Addition, at all concentrations used., followed by the volatile oil of lavender leaves with silicon nanoparticles. Where the percentage of inhibition of mycelium was 100% for the two treatments at the concentration 600ppm. While the essential oil of rosemary alone and loaded on silica nanoparticles gave lower percentage of inhibition of the fungus B. cinerea, where the two treatments did not give a 100% inhibition of growth at a concentration of 600 ppm. On the other hand, oily hexane extracts alone gave a low effect on the growth of B. cinerea fungus. While the oily hexane extracts loaded on silica nanoparticles of the studied plants gave a medium effect to inhibit the growth of fungus. The effect of essential oils and plant extracts and their loading on silica nanoparticles in inhibiting fungal growth increased with increasing concentration. We recommend the use of essential oils and oily hexane extracts and the product of loading them on nano-silicone of oregano and lavender plants as environmentally friendly bio-fungicides.